Mapping the distribution of stingray fishing grounds in the south west waters of Aceh during the east season - Afdhal Fuadi; Muhammad Arif; Rahmat Dianshar; Dimas Kusumayadi; Giovanni Oktavinanda (Depik, 2024)
One of the regions contributing to stingray fisheries production in Indonesia is Aceh province. The condition of stingray fisheries in Indonesia is currently facing challenges as the population is decreasing while the demand for stingray fishery resources domestically and abroad continues to increase. This condition certainly requires integrated stingray fisheries management efforts so that the rays population, especially in the waters of Aceh province, remains sustainable. This study aimed to determine the number, type, and distribution of stingray fishing grounds landed at the Ujong Baroh Fish Landing Base (PPI). The research was carried out in 2 stages; the first stage was to conduct a field survey by following fishermen directly to the sea and using interview questionnaires, and the second stage was to take satellite image data of sea depth, fishing location, and fishing distance and then make a map of stingray fishing ground distribution landed at Ujong Baroh Fish Landing Base, West Aceh. The number of stingray catches landed at Ujong Baroh Fish Landing Base during the study was 428, consisting of 11 species: 369 Maculabatis macrura, 42 Myliobatis tobijei, 14 Rhynchobatus australiae, 28 Dasyatis kuhlii, 8 Pateobatis uarnacoides, 7 Gymnura zonura, 6 Himantura leoparda, 2 Rhina ancylostoma, 2 Rhinobatos borneensis, 1 Aetobatus narinari, and 1 Taeniuriops meyeni. The results of the mapping analysis showed 18 distribution points of stingray fishing grounds and 4 fishing locations that obtained stingray catches, namely at the coordinates of 338.136'N and 9629.056'E, 42.144'N and 962.431'E, 416.599'N and 9532.000'E, 334.51472'N and 9625.80414'E.Keywords:MappingFishing GroundStingrayEastern Season